Basic Office Management Project: An Educational Intervention for the Training of Commercial Education Faculty - Ramírez Alfaro, Herminia (2018)
The proposal presented by the Proyecto Manejo Básico de Oficinas makes evident the importance of coordination between the strategic areas of the Universidad Nacional of Costa Rica, in this specific case, teaching and university extension. Innovative changes are proposed in the model of teacher training, making it flexible, more practical, more experiential, contextualized and according to the requirements, both social and student of Education Comercial curriculum. Furthermore, the model is enriched to increase opportunities for practice processes and training teachers to carry out their work with diverse populations, from youth, adults and seniors. A key point is how this experience of teacher training becomes both an educational intervention, which seeks to provide training opportunities to people in social disadvantage through non-formal education, and it favors the possibility of overcoming it personally, socially and occupationally. Therefore, this article intends to show the importance of an initiative that has enabled an innovative teacher training curriculum and address social needs through education by means of an extension and teaching project.